2008
DOI: 10.1371/journal.pone.0003974
|View full text |Cite
|
Sign up to set email alerts
|

Bitter Taste Receptors Influence Glucose Homeostasis

Abstract: TAS1R- and TAS2R-type taste receptors are expressed in the gustatory system, where they detect sweet- and bitter-tasting stimuli, respectively. These receptors are also expressed in subsets of cells within the mammalian gastrointestinal tract, where they mediate nutrient assimilation and endocrine responses. For example, sweeteners stimulate taste receptors on the surface of gut enteroendocrine L cells to elicit an increase in intracellular Ca2+ and secretion of the incretin hormone glucagon-like peptide-1 (GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
196
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(216 citation statements)
references
References 63 publications
(98 reference statements)
10
196
1
2
Order By: Relevance
“…Agonists recently identified (Dotson et al, 2008;Intelmann et al, 2009;Slack et al, 2010) were applied at EC 90 concentration. Because of low potency, agonists for hTAS2R5, hTAS2R7, and hTAS2R13 were used at their maximum applicable concentration that did not cause unspecific fluorescence signals in control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Agonists recently identified (Dotson et al, 2008;Intelmann et al, 2009;Slack et al, 2010) were applied at EC 90 concentration. Because of low potency, agonists for hTAS2R5, hTAS2R7, and hTAS2R13 were used at their maximum applicable concentration that did not cause unspecific fluorescence signals in control cells.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors likely play critical roles in nutrient detection. For example, bitter-taste receptors have been found to mediate glucose homeostasis (35) and secretion of the appetite-stimulating hormone ghrelin (70). Therefore, it is possible that variants in TAS2R genes could modulate appetite, food intake, and body weight through their functional roles in the gut.…”
Section: Prop Status Tas2r38 and Body Weightmentioning
confidence: 99%
“…[9][10][11][12] In the digestive tract, TAS2Rs are expressed in the endocrine cells of intestinal epithelial tissues and are known to participate in the secretion of incretins such as glucagon-like peptide-1 (GLP-1) and CCK. [13][14][15] Furthermore, it has been reported that bitter substances, such as denatonium, bind to tracheal smooth muscle, resulting in contraction of the bronchial tube. 16) We have previously reported that among the 25 human TAS2Rs (hTAS2Rs), the bitterness of catechins, which are precursors of theaflavins, is perceived by hTAS2R39 8) and hTAS2R14.…”
mentioning
confidence: 99%